Knowledge and attitudes towards complementary and alternative medicine among medical students in Turkey - APAYDIN KAYA, MEMNUNE ÇİĞDEM (BMC, 2012)
Objective: This study aims to examine knowledge and attitudes towards Complementary and Alternative Medicine among medical students in Turkey, and find out whether they want to be trained in Complementary and Alternative Medicine (CAM). Methods: A cross-sectional study was carried out between October and December 2010 among medical students. Data were collected from a total of seven medical schools. Findings: The study included 943 medical students. The most well known methods among the students were herbal treatment (81.2%), acupuncture (80.8%), hypnosis (78.8%), body-based practices including massage (77%) and meditation (65.2%), respectively. Acupuncture, aromatherapy, herbal treatment and meditation were better known among female participants compared to males (p < 0.05). Females and first year students, generally had more positive attitudes. A larger proportion of female students compared to male students reported that a doctor should be knowledgeable about CAM (p = 0.001), and this knowledge would be helpful in their future professional lives (p = 0.015). Positive attitudes towards and willingness to receive training declined as the number of years spent in the faculty of medicine increased. Conclusions: Majority of the medical students were familiar with the CAM methods widely used in Turkey, while most of them had positive attitudes towards CAM as well as willingness to receive training on the subject, and they were likely to recommend CAM methods to their patients in their future professional lives. With its gradual scientific development and increasing popularity, there appears a need for a coordinated policy in integrating CAM into the medical curriculum, by taking expectations of and feedback from medical students into consideration in setting educational standards.
Keywords: UNITED-STATES; EDUCATION; THERAPIES; ASTHMA; TRENDS